Efisiensi Biaya Produksi melalui Penggunaan Pakan Mandiri Berbasis Dedak pada Usaha Ayam Petelur di Desa Kutamandiri - Novianty Novianty; Diyani Fauziyah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
This study aims to analyze production cost efficiency through the use of self-formulated feed based on rice bran in laying hen farming in Kutamandiri Village. Feed costs represent the largest component of production expenses in laying hen enterprises, reaching up to 60–70% of total operational costs. The research employed a descriptive quantitative approach using primary data collected through observation, interviews, and cost-revenue recording during one production period. Data were analyzed using cost structure analysis and Revenue-Cost (R/C) ratio to determine business feasibility. The results indicate that the use of rice bran-based self-formulated feed reduced feed costs and lowered total production expenses. The calculated R/C ratio was 1.43, indicating that the enterprise is financially feasible and profitable. Additionally, the findings suggest that utilizing locally available feed resources such as rice bran can improve cost efficiency, reduce reliance on external feed supplies, and enhance the sustainability of small-scale laying hen enterprises. This research provides valuable insights for farmers in Kutamandiri Village and other similar agricultural communities looking to optimize production costs and improve their profitability by adopting cost-effective, locally sourced feed options.